Range walk and doppler walk compensation in DVB-T2 based passive radar - See Toh, Kevin Wei Huang (2015)
In moving target detections for a DVB-T2 based passive radar, utilizing long coherent integration times, the relatively high bandwidth of the DVB-T2 signal raises issues with respect to targets moving through range resolution cells, as well as manoeuvring targets sliding through Doppler resolution cells. If not properly dealt (compensated) with, these issues can result in target energy spreading across multiple range/Doppler resolution cells, thus lowering its signal-to-noise-ratio. The objective of the project is to study and understand the effects and the problems of range and Doppler walk in a passive radar. Subsequently, the student is to propose effective compensation techniques and algorithms to overcome the challenges.